Analisis Faktor Penyebab Turunnya Harga Jual Beli Sayuran Di Pasar Cakke Kecamatan Anggeraja Kabupaten Enrekang (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
The traditional market is located in Cakke, Anggeraja Subdistrict, Enrekang Regency whose market development has experienced a rapid increase. On this basis, it is necessary to examine the aspect of the sales system with the aim of knowing the analysis of the selling price of vegetables in the Cakke Traditional Market and to find out the sales system. This research is a qualitative research method with a descriptive approach by determining the location of the sample purposively and the sample of respondents as many as eight people whose samples were taken by census. The results obtained from this study show 1) Factor analysis of the Sale and Purchase Prices of Vegetables in the Cakke Traditional Market that if the harvest yields Vegetables are plentiful and buyers are not interested in eating vegetables, the price of vegetables will go down, and if the crops are sold through middlemen, vegetable prices tend to be high for the vegetable traders, but middlemen buy them at low prices. 2) The current sales system is a typical market in Cakke that accepts cash and credit. Use direct sales for this form of sales because they take vegetables harvested from farmers or traders and send them directly to the market or consumers. In the cash system it is done on the third channel (farmers à market). While in the credit sales system it is done on the first channel (farmers à middleman à wholesaler à market) and the second channel (farmer à middleman à market). The credit sales system has advantages, such as a well-defined market for vegetable distribution and well-structured interactions between farmers and middlemen.